1976
DOI: 10.1111/j.1365-2621.1976.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

TOASTING AND HEXANE:ETHANOL EXTRACTION OF DEFATTED SOY FLAKES Flavor of Flours, Concentrates and Isolates

Abstract: Flours and protein concentrates, prepared from defatted soybean flakes steamed up to 20 min before or after extraction with hexane:ethanol azeotrope 82/18 v/v, were presented to a 15-member trained taste paneL Flavors and odors were &scribed and rated for intensity on a scale of 1 to 10 where 1 is strong and 10 is bland. Azeotropic extraction for 6 hr by itself significantly affected flavor of flours and of concentrates so that they scored 7.4 and 6.8, respectively, compared to 4.0 for raw, hexane-defatted, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…As the lupine used was relatively low alkaloid (< 0.05%) it can be assumed that the poor results were due to the not removed hexane residue. If there was no further processing, hexane extraction alone could reduce the smell and nutritive value of the feed (Honig et al 1976). In the present experiment reproduction rates of the sows receiving soybean were better than those fed with lupines taking in account the weight of the piglets born.…”
Section: Discussionmentioning
confidence: 47%
“…As the lupine used was relatively low alkaloid (< 0.05%) it can be assumed that the poor results were due to the not removed hexane residue. If there was no further processing, hexane extraction alone could reduce the smell and nutritive value of the feed (Honig et al 1976). In the present experiment reproduction rates of the sows receiving soybean were better than those fed with lupines taking in account the weight of the piglets born.…”
Section: Discussionmentioning
confidence: 47%
“…Honig et al 65 studied the effect of toasting and solvent extractions (hexanerethanol, water, calcium hydroxide) in an attempt to improve nutrition and flavor of defatted soy flakes, protein concentrates, and protein isolates. They found that toasting and azeotropic extraction improved the flavor of soybean flour and protein concentrates, due to a reduction in grassy/beany, bitter, and astringent flavors.…”
Section: B Changes In Lipids During Processingmentioning
confidence: 99%
“…Toasting. Defatted flour was toasted with live steam for 10 min at 100~ in a preheated sterilizer autoclave and air dried for 24 h (8).…”
Section: Methodsmentioning
confidence: 99%
“…Sensory analysis. Sensory evaluation of the soy flour, toasted soy flour, soy flakes and soy concentrates was performed according to Honig et al (8) by eleven trained panelists. Overall odor and flavor intensities of the samples were based on a 10-point scale in which 1 was bland and 10 was strong.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation